Electrospun fibre based colorimetric probes for biological molecules - Mudabuka, Boitumelo (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
The thesis reports the use of electrospun nanofibres as a platform for the development of colorimetric probes. Three colorimetric probes in the form of electrospun nanofibre test strips were developed for the selective detection of ascorbic acid and dopamine because they are crucial biomolecules for physiological processes in human metabolism and usually coexist in biological samples. The simultaneous detection of the biomolecules is very important as their abnormal concentration levels would lead to diseases such as Parkinson's and schizophrenia. Different methods of incorporating detector agents into the nanofibre were exploited for the detection of the biomolecules. The methods included physical incorporation of nanoparticles, covalent bonding of ligand/dyes through surface modification of the fibres. The first colorimetric test strip for ascorbic acid was based on copper-gold alloy nanoparticles prepared in-situ and hosted in nylon6. The test strip showed selectivity in detecting ascorbic acid in the pH range 2 "“ 7. The suitability of fibres in hosting copper-gold alloy nanoparticles for the colorimetric detection of ascorbic acid was investigated using nylon6, poly(vinyl benzyl chloride)-styrene and cellulose acetate based test strips. All the test strips exhibited leaching and the nylon6 based test strip was found to be thermally stable up to 60 ËšC. The colorimetric performance of the test strips was maintained and neither was colour decay exhibited after 10 months of storage in a shelf. The test strip achieved an eye-ball limit of detection of 1.76 x10-2 mg L-1 and its suitability was demonstrated by the determination of ascorbic acid in fruit juices, urine, serum, and vitamin C tablets. The second colorimetric test strip for ascorbic acid and dopamine employed prussian blue synthesised in-situ in nylon6. Ascorbic acid turned the deep blue test strip to light blue at pH 3, and a faded navy blue colour at a pH range of 6 - 7 while dopamine changed the strip to purple at the same pH range. The versatility of the test strip was demonstrated by detecting ascorbic acid in commercial fruit juices as well as by detecting ascorbic acid as well as dopamine in fortified urine. The eye-ball detection limit of the Prussian blue test strip for ascorbic acid and dopamine was 17.6 mg L-1 and 18.9 mg L-1, respectively. The third method involved a covalent approach, where poly(vinylbenzyl chloride) nanofibers were post functionalised with 2-(2"²-pyridyl)-imidazole and iron(III) for the selective detection of ascorbic acid and dopamine. The eye-ball detection limit for ascorbic acid and dopamine was 17.6 mg L-1 and 18.9 mg L-1, respectively. The test strip was selective for dopamine, but the detection of ascorbic acid suffered from interference by glutathione. The application of the test strips was nevertheless demonstrated by the detection of ascorbic acid in fruit juices and dopamine in fortified urine. The developed test strips employing the three approaches were applied without sample pre-treatment and use of supporting equipment.
Keywords: Nanofibers; Vitamin C; Dopamine